2006
DOI: 10.4037/ajcc2006.15.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Recollections of Therapeutic Paralysis in the Intensive Care Unit

Abstract: • Background Neuromuscular blocking agents used for therapeutic purposes, such as facilitating mechanical ventilation and relieving life-threatening agitation, paralyze patients but leave them fully conscious. Aggressive sedation or analgesia is necessary to reduce awareness, relieve fear, produce comfort, decrease anxiety, induce unconsciousness, and minimize possible complications such as posttraumatic stress syndrome. Little information is available on the extent to which patients experience awareness durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Given the uncertainty that still exists pertaining to these important outcomes and the balance between benefits and potential harms, the panel decided that a weak recommendation was most suitable. If NMBAs are used, clinicians must ensure adequatepatient sedation and analgesia [400,401]; recently updated clinical practice guidelines are available for specific guidance [402].…”
Section: We Suggest Using Neuromuscular Blocking Agents (Nmbas) For ≤mentioning
confidence: 99%
“…Given the uncertainty that still exists pertaining to these important outcomes and the balance between benefits and potential harms, the panel decided that a weak recommendation was most suitable. If NMBAs are used, clinicians must ensure adequatepatient sedation and analgesia [400,401]; recently updated clinical practice guidelines are available for specific guidance [402].…”
Section: We Suggest Using Neuromuscular Blocking Agents (Nmbas) For ≤mentioning
confidence: 99%
“…Unintended (or accidental) awareness and recall are also a major concern during the use of NMBAs [110,111]. In patient interviews, feelings of dying, being tied down, and fear were expressed with the concomitant use of NMBAs.…”
Section: Complications From Neuromuscular Blockadementioning
confidence: 99%
“…Pain is a major stressor for patients in the intensive care unit (ICU; ; ; ). Indeed, recent studies have reported that more than 70% of patients recalled experiencing moderate to severe pain during their stay in the ICU (; ).…”
Section: Introductionmentioning
confidence: 99%